Naïve CD8+ T-Cells Engage a Versatile Metabolic Program Upon Activation in Humans and Differ Energetically From Memory CD8+ T-Cells - Nicoli, Francesco; Papagno, Laura; Frere, Justin J.; Cabral-Piccin, Mariela Pires; Clave, Emmanuel; Gostick, Emma; Toubert, Antoine; Price, David A.; Caputo, Antonella; Appay, Victor (Frontiers in Immunology, 2018)
Background: Characterization of the intracellular biochemical processes underlying priming of naïve CD8+ T-cells and the generation of effector and memory cells is key for our understanding of cellular immune responses and the development of immunotherapies. Studies in animal models have enlightened the metabolic processes and bioenergetics requirements that regulate the fate of distinct T-lymphocyte subpopulations. Complementing this knowledge in humans is necessary, especially as human T-lymphocyte subpopulations are defined differently, and can display distinct properties compared to mouse counterparts. Methods: We used here different orthogonal approaches to characterize the basal and activation-induced energetic requirements of naïve and phenotypically-defined subsets of human memory CD8+ T-cells. Expression levels of genes involved in metabolic processes, nutrient flux and the role of different biochemical pathways in T-cell receptor (TCR)-induced activation were investigated. Findings: Resting naïve CD8+ T-cells were largely quiescent, but showed a more rapid and intense upregulation of diverse energetic pathways, compared to more differentiated memory subsets, after ligation of surface-expressed TCRs. Of note, autophagy and the mTOR-dependent glycolytic pathway were simultaneously identified as critical mediators of antigen-driven priming in human naïve CD8+ T-cells. Moreover, the efficiency of naïve T-cell activation was dampened by the presence of neutral lipids and fatty acids. Interpretation: Profound metabolic differences are apparent as a function of CD8+ T-cell lineage and differentiation status, both at rest and in response to stimulation via the T-cell receptor TCR. These observations provide a metabolic roadmap of the CD8+ T-cell compartment in humans and revealed potentially selective targets for novel immunotherapies.